Plant density choice according to the sowing date of irrigated maize (Revista de Ciências Agroveterinárias, 2010)
This work aimed to determine the most suitable plant density for early and late sowing dates of irrigated maize in Brazilian regions with long growing season. Two experiments were carried out in Eldorado do Sul, southern Brazil. The first trial was set on 08/22/2006 (early sowing). It tested the hybrids D 2B587 and NB 4214 at four plant densities (55, 73, 91 and 110 thousand pl ha-1). The second experiment was set on 12/07/2007 (late sowing). It evaluated the hybrids D 2B587 and AS 1565 at the plant densities of 45, 60, 75 and 90 thousand pl ha-1. Both experiments were irrigated. At the early sowing, grain yield increased with the increment in plant density up to values ranging from 9.4 and 11 pl m-2, depending on the hybrid. When maize was sown in August, grain yield was greater than 15 t ha-1 at the higher plant densities. At the late sowing date, the highest kernel yields ranged from 10 to 11 t ha-1 and were obtained using plant populations of 9 pl m-2. The potential grain yield of irrigated maize in southern Brazil is reached using high plant densities, regardless of sowing date.
Keywords: Zea mays L.; Management practices; Grain yield; Plant arrangement.